2013
DOI: 10.3945/jn.113.177980
|View full text |Cite
|
Sign up to set email alerts
|

A High-Salt Diet Further Impairs Age-Associated Declines in Cognitive, Behavioral, and Cardiovascular Functions in Male Fischer Brown Norway Rats

Abstract: Aging-associated declines in cognitive, emotional, and cardiovascular function are well known. Environmental stress triggers critical changes in the brain, further compromising cardiovascular and behavioral health during aging. Excessive dietary salt intake is one such stressor. Here, we tested the effect of high salt (HS) on anxiety, learning-memory function, and blood pressure (BP) in male Fischer brown Norway (FBN) rats. Adult (A; 2 mo) and old (O; 20 mo) male rats were fed normal-salt (NS; 0.4% NaCl) or HS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
34
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 85 publications
(122 reference statements)
3
34
0
Order By: Relevance
“…In the same study, it was reported that the central administration of AT1 receptor blocker or tempol reduces the BP in sodium-sensitive rats more than in salt-resistant rats, which suggests that AngII-induced enhancement of central oxidative stress may be due to the sodium sensitivity. Also, salt loading caused an increase in hypothalamic mRNA expression subunits of NADPH oxidase p22, gp91, and p47 in Dahl sodium-sensitive rats [46] and unchanged MnSOD and Cu/ZnSOD levels in hippocampus and amygdale of FBN rats [47] and these findings support the suggestions mentioned above. Consistently, results of this study showed that HS diet in older rats significantly increased the hypothalamic gp91 protein, p22 mRNA levels compared with the young rats without altering the hypothalamic antioxidant levels and similarly, HS diet increased the NADPH oxidase activity more in the old rats.…”
Section: Discussionsupporting
confidence: 79%
“…In the same study, it was reported that the central administration of AT1 receptor blocker or tempol reduces the BP in sodium-sensitive rats more than in salt-resistant rats, which suggests that AngII-induced enhancement of central oxidative stress may be due to the sodium sensitivity. Also, salt loading caused an increase in hypothalamic mRNA expression subunits of NADPH oxidase p22, gp91, and p47 in Dahl sodium-sensitive rats [46] and unchanged MnSOD and Cu/ZnSOD levels in hippocampus and amygdale of FBN rats [47] and these findings support the suggestions mentioned above. Consistently, results of this study showed that HS diet in older rats significantly increased the hypothalamic gp91 protein, p22 mRNA levels compared with the young rats without altering the hypothalamic antioxidant levels and similarly, HS diet increased the NADPH oxidase activity more in the old rats.…”
Section: Discussionsupporting
confidence: 79%
“…As the population ages, identifying modifiable lifestyle factors that promote healthy cognitive aging is an increasingly pressing public health concern (2). Dietary sodium intake is one lifestyle factor that may affect cognitive function (3, 4), but its role in cognitive aging has not been thoroughly studied (5, 6). …”
Section: Introductionmentioning
confidence: 99%
“…Dietary sodium intake may also impair cognitive function independently of its effect on blood pressure. For example, studies in rodents (3, 4) suggest that high sodium diets impair spatial memory through an increase in oxidative stress in the hippocampus.…”
Section: Introductionmentioning
confidence: 99%
“…Chugh et al (16) showed in young (2 mo) and old (20 mo) male Fischer 344/BN rats that a HS (8% NaCl) diet for 4 wk increased systolic blood pressure by Ͻ5 mmHg. Therefore, it is unlikely that the age-associated effects were due to hypertension.…”
Section: Discussionmentioning
confidence: 98%
“…To maximize the sodium load, we maintained the rats on a LS diet for 2 wk before transferring them to a HS diet. We chose the Fischer 344/BN rat to avoid the confounds of age-and sodium-induced hypertension since these animals remain normotensive throughout their lifespan (7) and their blood pressure increases only marginally on a HS diet (16).…”
mentioning
confidence: 99%